Ionomer-like structure in mature oil paint binding media. Issue 96 (29th September 2016) - Hermans, Joen J.; Keune, Katrien; van Loon, Annelies; Corkery, Robert W.; Iedema, Piet D.
Abstract : We use ATR-FTIR and SAXS to demonstrate that oil paint binding media go through an ionomer-like state during ageing. Abstract : Infrared spectra of samples from oil paintings often show metal carboxylate bands that are broader and shifted compared to those of crystalline metal soap standards (metal complexes of long-chain saturated fatty acids). Using quantitative attenuated total reflection Fourier transform infrared spectroscopy (ATR-FTIR), it is demonstrated that the broad metal carboxylate band is typically too intense to be explained by carboxylates adsorbed on the surface of pigment particles or disordered metal complexes of saturated fatty acids. The metal carboxylate species associated with the broad bands must therefore be an integral part of the polymerized binding medium. Small-angle X-ray scattering (SAXS) measurements on model ionomer systems based on linseed oil revealed that the medium contains ionic clusters similar to more classical ionomers. These structural similarities are very helpful in understanding the chemistry of mature oil paint binding media and the potential degradation mechanisms that affect oil paintings.